Functionalization of metallic powder for performance enhancement. (September 2022) - Unnikrishnan, Rahul; Gardy, Jabbar; Spencer, Ben F.; Kurinjimala, Robin; Dey, Avishek; Nekouie, Vahid; Irukuvarghula, Sandeep; Hassanpour, Ali; Eisenmenger-Sittner, Christoph; Francis, John A.; Preuss, Michael
Graphical abstract: Chromium coating on a non-stainless low alloy steel powder improved the flowability and oxidation resistance. Highlights: A non-stainless low alloy (SA508 Grade 3) steel powder was coated with chromium by magnetron sputtering. There was a significant improvement in oxidation resistance after Cr coating. The tribo-electric charging of powder reduced with Cr coating resulting in improved flowability. Abstract: The oxidation state and surface properties of powder particles play a major role in the final properties of powder manufactured components. In the present study, the coating of a non-stainless low alloy (SA508 Grade 3) steel powder was explored to protect it from progressive oxidation while also studying the effects on powder flowability and electrical charging. The protective coating was applied by magnetron sputtering of chromium. The surface chemistries of both as-received and Cr coated powders were studied using X-ray photo electron spectroscopy (XPS). Accelerated oxidation tests were carried out on both uncoated and Cr coated powders to study the effects of coating on oxidation resistance. Hard X-ray photoelectron spectroscopy (HAXPES) analysis was used to measure oxygen pick up near the surface, showing significant reductions for the case of the Cr coated powder. The conductivity of the powder was found to increase with Cr coating. The flowability of the powder was characterised by the tapped density, the angle of repose (AOR) and a powder rheometer, and it was found to improve with a Cr coating, which can be attributed to reduced tribo-electrical charging and reduced cohesivity of the powder particles.